I love Russia : reporting from a lost country - Kosti͡uchenko, Elena, 1987- (Penguin Press, 2023)
"An unprecedented and intimate portrait of Russia, and a fearless cri de cœur for journalism in opposition to the global authoritarian turn To be a journalist is to tell the truth. I Love Russia is Elena Kostyuchenko's fearless and unrelenting attempt to document Putin's Russia as experienced by those whom it systematically and brutally erases: village girls recruited into sex work, queer people in the outer provinces, patients and doctors at a Ukrainian maternity ward, and reporters like herself. The result is a singular portrait of a nation, and of a young woman who refuses to be silenced. In March 2022, as a reporter for Russia's last free press, Novaya Gazeta, Kostyuchenko crossed the border into Ukraine to cover the war. It was her mission to ensure that Russians witnessed the horrors Putin was committing in their name. She filed her pieces knowing that should she return home, she would likely be prosecuted and sentenced to 15 years in prison. Yet, driven by the conviction that the greatest form of love and patriotism is criticism, she continues to write, undaunted and with eyes wide open. I Love Russia stitches together reportage from the past 15 years with personal essays, assembling a kaleidoscopic narrative that Kostyuchenko understands may be the last work from her country that she'll publish for a long time-perhaps ever. She writes because the threat of Putin's Russia extends beyond herself, beyond Crimea, and beyond Ukraine. We fail to understand it at our own peril"--